2023
DOI: 10.3390/asi6060100
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Electricity Demand Forecasting Using Deep Neural Networks: An Analysis for Thai Data

Kamal Chapagain,
Samundra Gurung,
Pisut Kulthanavit
et al.

Abstract: Electricity demand forecasting plays a significant role in energy markets. Accurate prediction of electricity demand is the key factor in optimizing power generation and consumption, saving energy resources, and determining energy prices. However, integrating energy mix scenarios, including solar and wind power, which are highly nonlinear and seasonal, into an existing grid increases the uncertainty of generation, creating additional challenges for precise forecasting. To tackle such challenges, state-of-the-a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…The influence of temperature on peak demand is negligible. This fact confirms the assertion made in article [59] that temperature has a negligible effect on commercial demand. When the temperature falls below 30 • C or rises above 35 • C, there is a significant fluctuation in demand during holidays.…”
Section: Temperature Vs Demandsupporting
confidence: 91%
“…The influence of temperature on peak demand is negligible. This fact confirms the assertion made in article [59] that temperature has a negligible effect on commercial demand. When the temperature falls below 30 • C or rises above 35 • C, there is a significant fluctuation in demand during holidays.…”
Section: Temperature Vs Demandsupporting
confidence: 91%
“…The study found that the Artificial Neural Network (ANN)-based Feedforward Neural Network (FNN) showed the minimum prediction error for the first scenario, while the Recurrent Neural Network (RNN)-based Gated Recurrent Network (GRU) was most effective for the second scenario. This research underscores the adaptability of deep learning models in handling complex, nonlinear, and seasonal data in electricity demand forecasting (Chapagain et al, 2023). Another innovative approach is presented in the study by Kim et al (2023), which developed a flexible renewable energy planning based on multi-step forecasting of interregional electricity supply and demand.…”
Section: Innovations and State-of-the-art Developments In Ai For Ener...mentioning
confidence: 95%
“…The research reveals that statistical models, Support Vector Machines, and Neural Networks are particularly effective in forecasting, demonstrating the potential of AI in managing the complexities of renewable energy integration (Tervo, 2023). Chapagain et al (2023) conducted a study on short-term electricity demand forecasting using deep neural networks, analyzing Thai data. The research constructed several models using deep AI networks in two different scenarios: one excluding weekends and holidays and the other without exclusions.…”
Section: Innovations and State-of-the-art Developments In Ai For Ener...mentioning
confidence: 99%
“…With these sophisticated systems, there has been a surge in the availability of system status information, enabling adaptive controllers to rely less on system knowledge. This shift has led to the emergence of data-driven controllers (DDCs) and model estimators [3,4]. Researchers typically categorize the adaptation of DDCs into online learning, offline learning, and hybrid approaches that combine both online and offline learning strategies.…”
Section: Introductionmentioning
confidence: 99%